2019
DOI: 10.4236/abcr.2019.81002
|View full text |Cite
|
Sign up to set email alerts
|

Extrinsic Risk Factors for Women Breast Cancer in Gaza Strip, Palestine: Associations and Interactions in a Case-Control Study

Abstract: Background: Worldwide, breast cancer (BC) is the most frequently diagnosed neoplastic disease in women around menopause that is the leading cause of DALYs, because it causes a significant reduction of these women's ability to function normally in everyday life. Methods: The present hospital-based case-control study was carried out between January and August 2018 using a structured questionnaire on 105 breast cancer women and 210 controls who are clinically free from breast cancer. Data about the study cases we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…The studies in [ 5 ] included 148 studies up until 2017 and looked at both studies that had no association and studies that had a positive association. The impact of hypertension on breast, colorectal, and endometrial cancers has also been reported in other studies [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ], but the most confirmed association has been made for renal cell carcinoma (RCC) [ 5 , 25 , 26 ]. One study observed the odds ratio (OR) with a 95% confidence ratio in individuals with self-reported hypertension in both men and women and found that hypertension was independently associated with a 40% increased risk of RCC compared to the refenced nonhypertensive patients (OR: 1.4; CI: 1.1–1.9 and OR: 1.0; CI: reference, respectfully) [ 26 ], and this increase was also observed in younger (20–39 years of age) hypertensive patients, where they saw a smaller but significant 16% increase in risk [ 27 ].…”
Section: Introductionmentioning
confidence: 52%
See 3 more Smart Citations
“…The studies in [ 5 ] included 148 studies up until 2017 and looked at both studies that had no association and studies that had a positive association. The impact of hypertension on breast, colorectal, and endometrial cancers has also been reported in other studies [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ], but the most confirmed association has been made for renal cell carcinoma (RCC) [ 5 , 25 , 26 ]. One study observed the odds ratio (OR) with a 95% confidence ratio in individuals with self-reported hypertension in both men and women and found that hypertension was independently associated with a 40% increased risk of RCC compared to the refenced nonhypertensive patients (OR: 1.4; CI: 1.1–1.9 and OR: 1.0; CI: reference, respectfully) [ 26 ], and this increase was also observed in younger (20–39 years of age) hypertensive patients, where they saw a smaller but significant 16% increase in risk [ 27 ].…”
Section: Introductionmentioning
confidence: 52%
“…Moreover, we found that even when adjusting for menopausal status, the association increased for postmenopausal women [ 44 ]. Through our further analysis [ 9 , 11 , 12 , 13 , 14 , 15 , 20 , 21 , 23 ], we saw a significant increase in risk for postmenopausal women, possibly because the present study mostly observed postmenopausal women and only included one study that observed a significant association found between hypertension and breast cancer over the entire sample regardless of menopausal status [ 12 ]. To understand the mechanisms underlying hypertension-caused organ-specific cancer, we here discuss the most vital mechanisms.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations